Low Frequency Air-Bone Gap in Meniere's Disease: Relationship With Magnetic Resonance Imaging Features of Endolymphatic Hydrops. Issue 6 (18th May 2022) - Pai, Irumee; Connor, Steve
Abstract : Objectives: The appearance of low-frequency air-bone gaps (LFABGs) in Meniere's disease (MD) is a recognized but relatively unexplored phenomenon. Two theories have been proposed to explain their etiology: increased perilymphatic pressure resulting in either reduced stapedial mobility or dampened transmission of acoustic energy, and direct contact between the dilated saccule and the stapes footplate. The aim of this study was to evaluate these two hypotheses by comparing delayed postgadolinium magnetic resonance imaging (MRI) features of two groups of patients with unilateral definite MD, those with and without LFABGs. Design: This retrospective case-control study was conducted at a tertiary otolaryngology unit in the United Kingdom. The study included 35 patients who satisfied the 2015 Barany criteria for unilateral definite MD. The cohort was divided into two groups, those with LFABGs (LFABG+ group) and those without (LFABG− group), according to the pure-tone audiometry performed within 6 months of MRI. Alternative potential causes for the LFABGs were excluded on the basis of otologic history, otoscopy, tympanometry, and/or imaging. Using a 4-hr delayed postgadolinium 3-dimensional fluid-attenuated inversion recovery sequence, two observers evaluated the severity of cochlear and vestibular endolymphatic hydrops (EH) and the presence of vestibular endolymphatic space contacting the oval window (VESCO). The air and bone conduction thresholds, ABGs and MRI features were compared between the LFABG+ and LFABG− groups. Where any of the variables were found to be significantly associated with the presence of ABGs, further analysis was performed to determine whether or not they were independent predictors. Continuous variables were compared using the independent t test if normally distributed, and the Mann–Whitney U test or Kruskall–Wallis test if not normally distributed. Categorical variables were compared with Pearson's Chi-squared test or Fishers/Fisher-Freeman-Halton exact tests. Results: There were 10 patients in the LFABG+ group (28.6%) and 25 patients in the LFABG− group (71.4%). The mean ABGs in the symptomatic ear at 500 Hz, 1 kHz, and 2 kHz were 15.1 dB ± 6.4, 10.5 dB ± 9.0, and 4.0 dB ± 7.7, respectively, in the LFABG+ group and 2.0 ± 5.8, 2.4 ± 4.4, and −0.8 ± 4.7 dB in the LFABG− group. The differences in ABGs between the two groups were statistically significant at all three test frequencies ( p < 0.001 at 500 Hz, p = 0.007 at 1 kHz, and p = 0.041 at 2 kHz). The presence of ABGs was significantly associated with both the grade of vestibular EH ( p = 0.049) and VESCO ( p = 0.009). Further analysis showed a statistically significant association between the grade of vestibular EH and VESCO ( p = 0.007), and only VESCO was an independent variable associated with the presence of LFABGs ( p = 0.045). Conclusions: The study findings add to the existing body of evidence that LFABGs are a true audiological finding in MD and allow us to propose a mechanism. Analysis of delayed gadolinium-enhanced MRI suggests that direct contact between the distended saccule and the inner surface of the stapes footplate is the more likely underlying pathophysiological mechanism for this audiometric phenomenon.